FAILURE ANALYSIS STUDY ON THE CUTTER BLADE OF POLYPROPYLENE PELLETER DRIVE - RUSLI, MOHAMAD FITRI (Universiti Teknologi Petronas, 2009)
This report basically discusses the Failure Analysis Study on Cutter Blade of Polypropylene Pelleter Drive. The objective of the project is to conduct failure analysis method on the cutter blade and to determine the causes of its failure. This report also discuss on the types wear and its wear mechanism. In this study, the author had obtained the cutter blades and background data of the sample. The author had conducted visual inspection of the sample, Vickers hardness test and microscopic inspection under optical microscope and scanning electron microscope or SEM. The result obtain from this study confirms that the blade materials is Titanium Carbide, high wear resistance material but brittle. This material data are obtained from the manufacturer datasheet. During preliminary stage, the samples show excessive and uneven wear on its cutting surface, some of the blades had chipped at titanium carbide tip. The chipped samples are selected and cut using electric discharge machining to obtain its cross section. These samples then are mounted to berkelite press then grinded and polished for microscopic evaluation. Microscopic inspection reveals the materials have voids in its microstructure. These voids tend to reduce its strength and the tip can break easily upon impact. Fractography result shows the tip fractures when being hit by foreign particles, the fractures are consistence with the cutting path of the blades. Mechanical testing using Vickers Hardness Test, the result obtained is Hv=797. The excessive wear on the cutter blades is suspected from poor operating procedure. During high melt index, polymer tends to produce tailings. To counter this problem the operator need to advance the pelleter rotor forward to the die plate. This resulting higher contact force and high wear rate. Lack of proper monitoring of cooling water entering the chamber may have lead to the chipping of TiC tip, debris may have come in between the blades during operation and collide with the tip. During cleaning of the chamber, the author had found sand inside the chamber. The outcome of these studies will provide recommendations in term of modifYing operating procedure and installing device to prevent from entering the pelleter assembly.